Mössbauer spectroscopy evidence of intrinsic non‐stoichiometry in iron telluride single crystals. Issue 4 (21st December 2016) - Kiiamov, Airat G.; Lysogorskiy, Yury V.; Vagizov, Farit G.; Tagirov, Lenar R.; Tayurskii, Dmitrii A.; Croitori, Dorina; Tsurkan, Vladimir; Loidl, Alois
Abstract : Fe1.05 Te parent compound for iron superconductor chalcogenides was studied with Mössbauer spectroscopy from room to liquid helium temperatures. Density functional ab initio calculations of electric field gradients revealed four non‐equivalent groups of iron atoms formed by their different local environment. The four‐group model consistently explains angular dependence of the Mössbauer spectra in single crystals as well as intensity asymmetry of the doublet absorption lines in powder samples at RT. Abstract : The FeTe parent compound for iron‐superconductor chalcogenides was studied applying Mössbauer spectroscopy accompanied by ab initio calculations of electric field gradients at the iron nuclei. Room‐temperature (RT) Mössbauer spectra of single crystals have shown asymmetric doublet structure commonly ascribed to contributions of over‐stoichiometric iron or impurity phases. Low‐temperature Mössbauer spectra of the magnetically ordered compound could be well described by four hyperfine‐split sextets, although no other foreign phases different from Fe1.05 Te were detected by XRD and microanalysis within the sensitivity limits of the equipment. Density functional ab initio calculations have shown that over‐stoichiometric iron atoms significantly affect electron charge and spin density up to the second coordination sphere of the iron sub‐lattice, and, as a result, four non‐equivalent groups of iron atoms are formed by their local environment. The resulting four‐group model consistently describes the angular dependence of the single crystals Mössbauer spectra as well as intensity asymmetry of the doublet absorption lines in powdered samples at RT. We suppose that our approach could be extended to the entire class of Fe 1 + y Se 1 − x Te x compounds, which contain excess iron atoms.